Hvordan gik det med lokaldemokratiet? - Welling Hansen, Sune (Politik, 2016)
The article reviews studies that have examined the local democratic consequences of the Danish Structural Reform, with focus on studies that have used the municipal amalgamations (which were part of the aforementioned reform) to study the relationship between the size of political systems and the quality of democracy in those systems. The reviewed studies tend to find negative effects of municipal size on the quality of local democracy, although the effects are weak to moderate in size. These results are consistent with the existing local government literature on the relationship between size and democracy, which also has shown that size does not matter much for the quality of democracy. If there indeed are differences between local democracies of different sizes then this has more to do with the characteristics of those who choose to live in these communities, than it has to do with size.